2009
DOI: 10.3945/ajcn.2009.28116
|View full text |Cite
|
Sign up to set email alerts
|

Low serum folate and vitamin B-6 are associated with an altered cancellous bone structure in humans

Abstract: The results of the present study indicate that low serum folate and vitamin B-6 concentrations, but not low serum vitamin B-12 concentrations, are associated with an altered morphology of human bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 29 publications
0
26
0
1
Order By: Relevance
“…Evidence to support an effect of folate on bone While folate has been linked to BMD and a reduced fracture risk (54,70) , there is limited evidence to support a direct mechanistic effect of folate on bone, although one study reported a reduced trabecular thickness of bone in individuals with low folate status v. those with higher status (71) . Folate could have an indirect role on bone remodelling cells via its metabolic link (as a methyl source) to the methylation of DNA, proteins and other molecules and there is evidence, albeit somewhat inconsistent, to support a reduced methylation capacity as a pathomechanism responsible for poor bone health (57,(72)(73)(74) .…”
Section: Evidence To Support An Effect Of Homocysteine On Bonementioning
confidence: 99%
“…Evidence to support an effect of folate on bone While folate has been linked to BMD and a reduced fracture risk (54,70) , there is limited evidence to support a direct mechanistic effect of folate on bone, although one study reported a reduced trabecular thickness of bone in individuals with low folate status v. those with higher status (71) . Folate could have an indirect role on bone remodelling cells via its metabolic link (as a methyl source) to the methylation of DNA, proteins and other molecules and there is evidence, albeit somewhat inconsistent, to support a reduced methylation capacity as a pathomechanism responsible for poor bone health (57,(72)(73)(74) .…”
Section: Evidence To Support An Effect Of Homocysteine On Bonementioning
confidence: 99%
“…Laboratory analysis was performed the morning after injury in a fasting state. Eleven bone specific parameters reflecting bone metabolism were examined: intact PTH [ 10 ], 25-hydroxy vitamin D3 (25-OH-D3) [ 11 ], beta-crosslaps (ß-CTX), pyridinoline in urine, desoxypyridinoline in urine (DPD) [ 10 , 12 ], procollagen type 1 N propeptide (PINP) [ 10 ], creatinine in urine [ 13 ], estradiol [ 10 ], homocysteine, vitamin B12 and folate [ 14 , 15 ]. Every pathologic aberration from the standard value was assessed with one point.…”
Section: Methodsmentioning
confidence: 99%
“…Holstein et al 14 concluded that only markers of bone formation (osteocalcin) were increased in individuals who had higher serum levels of B-complex vitamins, including B12. However, in the same study, no significant differences were found in the trabecular thickness of individuals with high and low serum levels of vitamin B12, thus questioning the true role of vitamin B12 in the turnover of bone biomarkers.…”
Section: Interventions With %Cho <20% and >40%mentioning
confidence: 99%